Asesmen Psikologis untuk Kebutuhan Pendidikan Agama Islam (PAI) - Saimin; Mufida Cholil (TSAQOFAH, 2026)
Although assessment in Islamic Religious Education (PAI) plays an important role in comprehensively understanding students’ development, its practice still tends to focus on measuring cognitive learning outcomes, while emotional, social, moral, and spiritual conditions have not received balanced attention. This study aims to analyze the concepts, dimensions, instruments, integration strategies, and ethical challenges of psychological assessment in supporting PAI learning. This study employed a qualitative approach using a literature review method. Data were obtained from books, journal articles, research findings, and scholarly documents discussing educational psychology, Islamic psychology, learning assessment, religiosity, emotional intelligence, and student development. The data were analyzed thematically through the stages of selection, classification, comparison, synthesis, and conclusion drawing. The findings show that psychological assessment in PAI learning needs to be implemented multidimensionally by encompassing cognitive-religious, emotional-spiritual, social-interpersonal, behavioral-moral, and innate disposition and personal potential dimensions. Assessment data can be collected through psychological scales, observation, interviews, portfolios, reflective journals, and sociometry by involving multiple sources of information. Assessment results can be used to design differentiated learning, determine appropriate forms of support, and make professional referrals. Its implementation must consider instrument validity, alignment with Islamic values and culture, data confidentiality, participant consent, the limits of teachers’ competence, and the prevention of religious labeling. This study concludes that multidimensional, ethical, and collaborative psychological assessment can strengthen PAI learning that is more humane, responsive, and oriented toward students’ holistic development.